The use of supplementary materials in EFL classes: A comparative analysis of public and private high schools - Cadena Aguilar, Albania Johanna (2012)
This study is about the use of supplementary materials in English foreign language (EFL) classes with a comparative analysis of public and private high schools in Guayaquil. Its purpose is to find out whether or not teachers use supplementary materials, and if they do, how pertinent, appropriate, and qualified they are. This research was conducted in private and public high schools. It consisted of observing 30 EFL classes from 1st, 2nd and 3rd Senior years. This study was qualitative and quantitative approached. Data was collected through observation forms, questionnaires, and surveys. For the analysis and interpretation of results, the qualitative analysis was done taking into consideration pertinence, appropriateness and quality of each type of supplementary material used. And quantitative analysis was done to determine and analyze the frequency of supplementary materials used in the three observed courses. The results revealed that total frequency of use of supplementary materials in the EFL classes were the same in both high schools. However, the whiteboard was mostly used in the public high school and videos were the resource commonly used in the private institution.